ATSAR ISTIKHDAM MURABBA’ AL-KALIMAT FI TA’LIM MUFRADAT WA TA’ALLUMIHA - Nur Fitri; Siti Uriana Rahmawati (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
This study attempted to prove the influence of the use of the word square in teaching vocabulary at MTsN I South Tangerang City, i.e., to prove students’ ability of two classes, before and after using the learning model of word square in teaching learning vocabulary. The research is descriptive-quantitative using the experimental method. The sample of this study was the students of VIII-8 and VIII-11 class in the academic year of 2016-2017. Data collection techniques were observation, interview, vocabulary test, and questionnaire for students of the experimental class. Based on the results of data analysis, the average score of the experimental class was 16,11 and the average score of the control class was 10,65. The score of to was 2,70 and the score of tt was 1,67; then, to was greater than tt. Thus, the use of learning model of word square in teaching vocabulary was significantly effective.